Respiratory Adherence Care Enhancer Questionnaire: Identifying Self-Management Barriers of Inhalation Corticosteroids in Asthma - Visser, Claire D.; Linthorst, Jip M.; Kuipers, Esther; Sont, Jacob K.; Lacroix, Joyca P. W.; Guchelaar, Henk-Jan; Teichert, Martina (Frontiers in Pharmacology, 2021)
Introduction: Suboptimal self-management of inhaled corticosteroids (ICS) in asthma patients is frequently observed in clinical practice and associated with poor asthma control. Driving factors for suboptimal self-management are complex and consist of a range of behavioral barriers (cognitive, affective and practical) with a considerable inter-individual variability. Identification of individual barriers facilitates the use of corresponding behavior change techniques and tailored care to improve asthma treatment outcomes. Objective: This study describes the development and validation of the ‘Respiratory Adherence Care Enhancer’ (RACE) questionnaire to identify individual barriers to self-management of ICS therapy in asthma patients. Methods: The development included: 1) an inventory of self-management barriers based on a literature review, 2) expert assessment on relevance and completeness of this set, linking these barriers to behavioral domains of the Theoretical Domains Framework (TDF) and 3) the formulation of corresponding questions assessing each of the barriers. A cross-sectional study was performed for validation. Primary care asthma patients were invited to fill out the RACE-questionnaire prior to a semi-structured telephonic interview as golden standard. Barriers detected from the questionnaire were compared to those mentioned in the interview. Results: The developed questionnaire is made up of 6 TDF-domains, covering 10 self-management barriers with 23 questions. For the validation 64 patients completed the questionnaire, of whom 61 patients were interviewed. Cronbach’s alpha for the consistency of questions within the barriers ranged from 0.58 to 0.90. Optimal cut-off values for the presence of barriers were determined at a specificity between 67% and 92% with a sensitivity between 41% and 83%. Significant Areas Under the Receiver Operating Curves values were observed for 9 barriers with values between 0.69 and 0.86 (p-value <0.05), except for ‘Knowledge of ICS medication’ with an insignificant value of 0.53. Conclusion: The RACE-questionnaire yields adequate psychometric characteristics to identify individual barriers to self-management of ICS therapy in asthma patients, facilitating tailored care.